Bikini versus Traditional Incision Direct Anterior Approach: Is There any Difference in Soft Tissue Damage?. Issue 4 (July 2017) - Lanting, Brent A.; Hartley, Kirk C.; Raffoul, Adam J.; Burkhart, Timothy A.; Sommerville, Lyndsay; Martin, Glynn R.; Howard, James L.; Johnson, Marjorie
Introduction: The direct anterior approach for total hip replacements has reported advantages of improved early function and muscle preservation. In an effort to improve healing and cosmesis, a change in the orientation of the incision has been proposed. Traditionally, the skin incision is in-line with the tensor fasciae latae muscle belly. The bikini incision is orthogonal to this orientation. The hypothesis was that muscle damage would be increased by using the bikini incision. Methods: A traditional or bikini incision was performed on 18 cadaveric hips. On each of the 9 specimens, the traditional incision was performed on 1 side, and a bikini incision on the contralateral hip, with an even distribution of right or left side. Blinded anatomists performed the hip dissections, and assessed for muscle damage as well as for damage to the lateral femoral cutaneous nerve. Results: No difference in muscle damage was identified in the tensor fasciae latae between muscle groups. Muscle damage was very minimal to the gluteus medius and minimus. Damage to the lateral femoral cutaneous nerve occurred equally for both the bikini and traditional skin incisions. Conclusions: The bikini incision for the direct anterior approach to the hip can be performed safely, with no increase in muscle damage or damage to the lateral femoral cutaneous nerve compared to the traditional incision.